2007
DOI: 10.1002/ange.200605248
|View full text |Cite
|
Sign up to set email alerts
|

Die gerüststarre Aminosäure β‐Acc verleiht Integrinliganden Aktivität und Selektivität

Abstract: Der Einbau des rigiden Bausteins (+)‐β‐Acc (Acc=Aminocyclopropancarbonsäure) in ein cyclisches RGD‐Peptid führt wegen der hierdurch induzierten konformativen Einschränkungen zu hoch affinen Liganden für das Integrin αvβ3. Die Peptide 1 und 2 enthalten die enantiomeren Bausteine (+)‐ (blau) bzw. (−)‐β‐Acc (rot). Das aktivere Peptid 1 inhibiert die αvβ3‐vermittelte Zelladhäsion an Vitronectin mit einem IC50‐Wert von 20 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…Unserem Wissen nach ist dies das erste cyclische Peptid basierend auf einer retro‐RGD‐Sequenz, das eine nanomolare Aktivität und Selektivität für α5β1 zeigt. Es gibt lediglich das natürliche Peptid c (CRRETAWAC)19 und cyclische RGD‐Peptide mit β‐Aminosäuren,20, 21 für die in Zellstudien ähnlich gute Aktivitäten und Selektivitäten gezeigt wurden. Dieses biologische Profil kann zur Aufklärung der molekularen Wirkungsweise von Cilengitid beitragen.…”
Section: Methodsunclassified
“…Unserem Wissen nach ist dies das erste cyclische Peptid basierend auf einer retro‐RGD‐Sequenz, das eine nanomolare Aktivität und Selektivität für α5β1 zeigt. Es gibt lediglich das natürliche Peptid c (CRRETAWAC)19 und cyclische RGD‐Peptide mit β‐Aminosäuren,20, 21 für die in Zellstudien ähnlich gute Aktivitäten und Selektivitäten gezeigt wurden. Dieses biologische Profil kann zur Aufklärung der molekularen Wirkungsweise von Cilengitid beitragen.…”
Section: Methodsunclassified
“…Later, the same group reported the synthesis, structural analysis and biological evaluation of pentapeptides containing the constrained cis-βaminocyclopropanecarboxylic acid (β-Acc). [89] The cyclic pentapeptide c(RGD-(+)-β-Acc-V) (Table 1) exhibited a very high activity for αvβ3 (20 nM) in a cellular adhesion assay of WM115 cells to FN and good selectivity against α5β1 (1.5 µM, 75-fold) of K562 cells on FN. In 2008, Pramanik et al reported that a lipopeptide with the tetrapeptide sequence RGDK could selectively target genes to the α5β1 integrin receptor in vitro.…”
Section: N-methylation Of C(rgdfv) Led To the Drug Candidate Cilengitmentioning
confidence: 99%
“…[9] Among the successful approaches, we would like to mention the g-amino acid RGD peptidomimetics containing a g-aminocyclopentane carboxylic acid or a 4aminoproline residue (14-membered ring), [10] the azabicyclic lactam RGD peptidomimetics (15-membered ring, with the scaffold mimicking a constrained dipeptide, e.g., ST1646), [11] and the b-amino acid RGD peptidomimetics, embodying b 3homoamino acids [12] (13-membered ring) or a cis-b-aminocyclopropane carboxylic acid (16-membered ring). [13] Up to now, a large number of linear or cyclic peptidic and peptidomimetic ligands have been developed, which are all related to the common recognition motif RGD [14] and a few potent ligands are presently in different stages of clinical trials for cancer therapy. Notwithstanding these recent achievements, the discovery of new ligands displaying high activity and selectivity together with an optimal pharmacological profile still remains a challenge.…”
Section: Introductionmentioning
confidence: 99%